Investigation of Antidiabetic, Antihyperlipidemic, and In Vivo Antioxidant Properties of Sphaeranthus indicus Linn. in Type 1 Diabetic Rats: An Identification of Possible Biomarkers. (26th September 2010) - Ramachandran, S.; Asokkumar, K.; Uma Maheswari, M.; Ravi, T. K.; Sivashanmugam, A. T.; Saravanan, S.; Rajasekaran, A.; Dharman, J.
Abstract : The present investigation was aimed to study the antidiabetic, antihyperlipidemic, and in vivo antioxidant properties of the root of Sphaeranthus indicus Linn. in streptozotocin- (STZ-) induced type 1 diabetic rats. Administration of ethanolic extract of Sphaeranthus indicus root (EESIR) 100 and 200 mg/kg to the STZ-induced diabetic rats showed significant (P < .01 ) reduction in blood glucose and increase in body weight compared to diabetic control rats. Both the doses of EESIR-treated diabetic rats showed significant (P < .01 ) alteration in elevated lipid profile levels than diabetic control rats. The EESIR treatment in diabetic rats produced significant increase in superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and decrease in thiobarbituric acid reactive substances (TBARS) levels than diabetic control rats. Administration of EESIR 200 mg/kg produced significant (P < .01 ) higher antioxidant activity than EESIR 100 mg/kg. The high performance liquid chromatography (HPLC) analysis of EESIR revealed the presence of biomarkers gallic acid and quercetin. In conclusion, EESIR possess antidiabetic, antihyperlipidemic, and in vivo antioxidant activity in type 1 diabetic rats. Its antioxidant and lipid lowering effect will help to prevent diabetic complications, and these actions are possibly due to presence of above biomarkers.